Kemampuan Penyusunan Dan Penggunaan Lembar Kerja Siswa Guru Mapel Ipa Kelas VII Dan VIII Kurikulum 2013 Di SMP Negeri 1 Sawit Tahun Pelajaran 2014/2015 - Fahira, Fani; , Dra. Hariyatmi, M.Si (2015)
The teacher as a facilitator should be able to use and choose a good learning resources. One source of learning that learning is used mainly in LKS. This study aims to determine the ability of teachers to use the worksheets in science teaching classes VII and VIII based curriculum in 2013 in SMP Negeri 1 Oil Year 2014/2015. This type of research is descriptive qualitative data collection techniques in the form of documentation LKS science teacher, observation and interviews with science teachers in SMP Negeri 1 Oil. Data obtained in the form of the preparation and use of worksheets by science teachers, were analyzed using descriptive statistics. The result showed that the average preparation of worksheets on the componentstructure of 66%, 92% coverage of material, the material accuracy of 79%, 64% appearance, linguistic component of 81%, 79% presentation techniques, terms dedaktif 72%, 71% construction requirements, terms 81% technical. While the average use of the usability component LKS LKS at 91%, the implementation of the use of LKS 94%, 92% compliance with procedures, presentation 88%, 75% linguistic components, skills of teachers 85%, and the interest of learners 85%. It can be concluded that the science teacher preparation worksheets included in the excellent category (76.1%), and the use of worksheets by a science teacher is very good category (87.2%). Key word: using, LKS, theacer capability, kurikulum 2013, IPA